2014
DOI: 10.1002/ejp.545
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of hypnosis compared with biofeedback for adults with chronic low back pain

Abstract: The findings indicate that two sessions of self-hypnosis training with audio recordings for home practice may be as effective as eight sessions of hypnosis treatment. If replicated in other patient samples, the findings have important implications for the application of hypnosis treatment for chronic pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 25 publications
2
55
0
5
Order By: Relevance
“…Mindfulness-based interventions and hypnosis have been found to be sustainable, economically viable interventions, that can be used for the effective management of emotional, behavioral, and physiological symptomology, including chronic pain (Cuellar, 2008; Tan et al, 2015). While the similarities and differences of these two approaches has been the subject of debate, this study found that measures of the theorized unique moderators underlying the two approaches are distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness-based interventions and hypnosis have been found to be sustainable, economically viable interventions, that can be used for the effective management of emotional, behavioral, and physiological symptomology, including chronic pain (Cuellar, 2008; Tan et al, 2015). While the similarities and differences of these two approaches has been the subject of debate, this study found that measures of the theorized unique moderators underlying the two approaches are distinct.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized clinical trial, it looked into the difference between hypnosis for chronic low back pain and hypnosis with biofeedback techniques, it showed that biofeedback with hypnosis is significantly more effective than hypnosis alone [33].…”
Section: Biofeedbackmentioning
confidence: 99%
“…D'autres travaux vont dans ce sens, c'est-à-dire une meilleure acceptation par les patients de leur pathologie chronique, une amélioration des stratégies d'adaptation à leur situation et un renforcement de leur implication dans les soins, dans leur santé, notamment pour l'acupuncture [20][21][22]. De la même façon, si l'hypnose et la méditation, classées dans les approches psychocorporelles des médecines complémentaires, montrent une certaine efficacité sur le symptôme évalué directement par des études, néanmoins de qualité variable et assez hétérogènes [23][24][25][26][27], leurs actions sur les aspects cognitifs et affectifs de la douleur paraissent supérieures [28]. Certains auteurs proposent d'ailleurs une action en tandem de ces deux approches sur les aspects d'acceptation et de modulation cognitive [29].…”
Section: Quelles Sont Ces Médecines Complémentaires ?unclassified